2001
DOI: 10.1046/j.1365-3083.2001.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Th2 Regulatory T‐Cell Control of Th1 Autoimmunity

Abstract: The Th1/Th2 concept brought an attractive explanation of the active self tolerance which appears to control the onset of pathogenic autoimmunity. New data coming from various independent horizons indicate that self immunoregulation could also depend to a large extent on non‐Th2 cells. Original data derived from the day‐3‐thymectomy model, selective T‐cell lymphocytopenia and nonobese diabetic mice are discussed in an effort to analyze similarities and differences in phenotype (CD25, CD62L and CD45RB) and cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 84 publications
(95 reference statements)
0
26
0
Order By: Relevance
“…63 The IFN-␥ axis can be antagonized by T H 2-type cytokines, especially IL-4, 70 as well as by regulatory cytokines, such as TGF-␤1 or IL-10. 71 As noted above, these cytokines exert some effects directly on T cells, shutting off IFN-␥ secretion, but IL-4 and regulatory cytokines also exert effects on APCs, eg, turning off IL-12 production. The signals which initiate these alternative responses are less clear than those which turn on the IFN-␥ axis; the T H 2 response has sometimes been described as a default pathway.…”
Section: T H 1 Effector Cells and Cd8mentioning
confidence: 96%
“…63 The IFN-␥ axis can be antagonized by T H 2-type cytokines, especially IL-4, 70 as well as by regulatory cytokines, such as TGF-␤1 or IL-10. 71 As noted above, these cytokines exert some effects directly on T cells, shutting off IFN-␥ secretion, but IL-4 and regulatory cytokines also exert effects on APCs, eg, turning off IL-12 production. The signals which initiate these alternative responses are less clear than those which turn on the IFN-␥ axis; the T H 2 response has sometimes been described as a default pathway.…”
Section: T H 1 Effector Cells and Cd8mentioning
confidence: 96%
“…Type 1 regulatory (Tr1) T cells mainly exert their suppressive activity through the secretion of IL-10 ( Roncarolo et al, 2001), a potent immunosuppressive cytokine (Moore et al, 2001), while Th3 cells suppress cell activation through TGFβ release (Bach, 2001;Chen et al, 1994). Both in vitro and in vivo studies with recombinant IL-10 and neutralizing antibodies revealed pleiotropic activities of IL-10 on B, T, and mast cells (Moore et al, 2001).…”
Section: B Tr1 Regulatory T Cells and Il-10 Productionmentioning
confidence: 99%
“…Three major classes of immunoregulatory T cells have been described (18): Th2/Th3 cells (19,20), CD4 + CD25 high cells (21,22), and Tr1 cells (23). The immunoregulatory Tr1 cells were identified by Roncarolo and coworkers (24) and secrete IL-10, a potent immunosuppressive cytokine with pleiotropic activities on B, T, and mast cells.…”
Section: Introductionmentioning
confidence: 99%